Self-help measures against cyber threats in international law:: Special reference to the possible adoption of collective countermeasures - Piernas López, Juan Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article analyses the measures that subjects of international law can legitimately take to respond to malicious cyber activities. In particular, the article examines the main measures of self- help provided for by International law, namely retorsion, countermeasures and self-defence in response to cyber-attacks. To this end, the article first studies the question of retorsion in this area. Secondly, the issue of countermeasures is analysed, with particular reference to the possibility of adopting collective countermeasures in the light of recent positions adopted by States and certain institutions and bodies of the European Union. Thirdly, the possibility of acting in self-defence in response to a cyber-attack is examined. Finally, a number of concluding remarks are included.
Keywords: self-help; cyberspace; International law; retaliation; countermeasures; self-defence